(3JLQjO GdJaSjQ ef GdcTGa eY RjGOI fcJ dWGas - (3Ydj Hf eMeO Hf CHi GdbGSe GdRjOis; (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj , GdTjQGRj GdHjVGhj, CHh SYjO CHh GdNjQ fGUQ GdOjf,J (B685 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CfYe YdjfG HGdbQBf , haVdfG HcdGeg , hgOGfG Edi GdEjeGf s
(3BNQgG (B:s
(3hjfJgi HJaSjQ ShQI Gdcga , hBNQg (B( (3bGd GdMSf CQGO Hbhdg hdG jTQc CdG jYHO ef Gddg ZjQg Je GdcJGH (B) s
(3HBNQg YGQjI eDQNI SfI (B1250(3g`s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B110 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B298s
Keywords: (3GdJaSjQ hYdhe GdbQBfs